The Molecular Basis of a Case of γ-Glutamylcysteine Synthetase Deficiency - Beutler, Ernest; Gelbart, Terri; Kondo, Takahito; Matsunaga, Alison T. (Blood, 1999)
γ-Glutamylcysteine synthetase catalyzes the first step in glutathione synthesis. The enzyme consists of 2 subunits, heavy and light, with the heavy subunit serving as the catalytic subunit. A patient with hemolytic anemia and low red blood cell glutathione levels was found to have a deficiency of γ-glutamylcysteine synthetase activity. Examination of cDNA from the patient and her mother showed that she was homozygous and that her mother was heterozygous for a A→T transversion at nt1109 producing a deduced amino acid change of His370Leu. The partial genomic structure of the catalytic subunit of γ-glutamylcysteine synthetase (GLCLC) was determined, providing some intron/exon boundaries to make it possible to sequence an affected part of the coding region from genomic DNA. The 1109A→T mutation was not present in the DNA of 38 normal subjects. In the course of these studies we found a diallelic polymorphism in nt +206 of an intron and another polymorphism that consisted of a duplication of a CAGC at cDNA nt1972-1975 in the 3′ untranslated region. The 2 polymorphisms were found to be only in partial linkage disequilibrium.